A Comparative Study of the Methods to Assess Occupational Noise Exposures of Fish Harvesters - Giorgio Burella; Lorenzo Moro (Elsevier, 2021)
Background: Noise-induced hearing loss is a well-known occupational disease that affects many fish harvesters from many fisheries worldwide, whose risk factor is prolonged exposure to hazardous noise levels. To date, academic research activities and regulatory bodies have not provided any comparative analysis among the existing methods to assess noise exposure levels of fish harvesters. This paper provides a comparison of four relevant assessment methods of noise exposure, examining the results of a measurement campaign performed onboard small fishing vessels from Newfoundland and Labrador. Methods: We traveled onboard 11 vessels engaged in multiple fisheries from Newfoundland and Labrador and performed extensive noise exposure surveys using the simplified International Maritime Organization method, the full-day measurement method, and the two methods provided by ISO 9612:2009, the task-based method and job-based method (JBM). Results: The results showed that the four methods yield similar values when the noise components are dominated by the engine and auxiliaries (steady-state sources); when noise components are dominated by the fishing gear, task-based method and the simplified International Maritime Organization method estimates are less accurate than JBM, using full-day measurements as baseline. Conclusion: The JBM better assesses noise exposure in small-scale fisheries, where noise exposure has significant variance and uncertainties on the exposure levels are higher.